2015
DOI: 10.2166/wst.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic removal of 2-nitrophenol using silver and sulfur co-doped TiO2 under natural solar light

Abstract: To overcome the drawback of poor solar light utilization brought about by the narrow photoresponse range of TiO₂, a silver and sulfur co-doped TiO₂was synthesized. Using the prepared catalyst, solar photocatalytic degradation of 2-nitrophenol (2-NP) by a TiO₂-based catalyst was studied for the first time. Effects of the co-doping on the structural, optical and morphological properties of the synthesized nanoparticles were investigated by different characterization methods: X-ray diffraction, N2 adsorption-deso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Several scientific studies on the modification and development of TiO 2 catalyst in order to increase its visible light sensitivity have been reported over the past decades . Doping TiO 2 with metals and non‐metals (such as silver and sulphur respectively) has been known as an efficient strategy to extend its optical response from UV to visible light range . Doping these impurities into the TiO 2 matrix can decrease the band gap of the semiconductor and increase the photocatalytic activity of TiO 2 under the visible light significantly without modifying its surface properties .…”
Section: Introductionmentioning
confidence: 99%
“…Several scientific studies on the modification and development of TiO 2 catalyst in order to increase its visible light sensitivity have been reported over the past decades . Doping TiO 2 with metals and non‐metals (such as silver and sulphur respectively) has been known as an efficient strategy to extend its optical response from UV to visible light range . Doping these impurities into the TiO 2 matrix can decrease the band gap of the semiconductor and increase the photocatalytic activity of TiO 2 under the visible light significantly without modifying its surface properties .…”
Section: Introductionmentioning
confidence: 99%
“…6. The photo-generated electron competes with the substrate to react with the adsorbed hydroxyl radical according to Equation (10). As no oxygen exists to react with the formed hydroxide, it can transfer the electron back to the photocatalyst and convert to hydroxyl radical.…”
Section: The Oxidation Reaction Occurs On the Surface Of Semiconductormentioning
confidence: 99%
“…8 Photocatalytic reactions have been considered as a promising alternative for future chemical conversion, since the discovery of water photolysis on a TiO 2 electrode by Fujishima and Honda. 9 Titanium-based photocatalysts are the most recognized [10][11][12][13] and alternative photocatalysts are not still reliable due to issues such as their stability, cost, toxicity, availability, and activity under full solar spectrum. 14…”
mentioning
confidence: 99%
“…Among various transition metal and non‐metal doping agents, silver and sulphur have been recognized as promising candidates . Thereby, the co‐doping of TiO 2 with Ag and S can exhibit the significant enhancement of the photocatalytic activity under visible light due to their synergistic effect . In addition, it has been reported that by incorporating polyethylene glycol (PEG) as the chelating agent in the synthesis process of a titanium dioxide‐based photocatalyst, macroporous powders with large surface areas can be obtained .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to achieve a comprehensive understanding of the H 2 O 2 ‐assisted photocatalytic process, investigating the interaction effects is as substantial as the individual effects. For this purpose, the response surface methodology (RSM) based on a statistical design of experiments (DOE) can be used . Therefore, this technique can be utilized to find the interaction effects between the parameters (i.e., photocatalyst and H 2 O 2 ) and obtain optimum conditions.…”
Section: Introductionmentioning
confidence: 99%